Solar Energy Conversion: Hole‐Accepting‐Ligand‐Modified CdSe QDs for Dramatic Enhancement of Photocatalytic and Photoelectrochemical Hydrogen Evolution by Solar Energy (Adv. Sci. 4/2016). Issue 4 (April 2016) - Li, Xu‐Bing; Liu, Bin; Wen, Min; Gao, Yu‐Ji; Wu, Hao‐Lin; Huang, Mao‐Yong; Li, Zhi‐Jun; Chen, Bin; Tung, Chen‐Ho; Wu, Li‐Zhu
Abstract : Water‐splitting by sunlight to produce H2 offers one of the best solutions to meet future energy demands. In order to develop suitable catalysts, L.‐Z. Wu and co‐workers have established a facile approach, detailed in article 1500282, involving simple integration of hole‐accepting ligands onto quantum dots (QDs), to dramatically improve the H2 evolution efficiency from QDs both in aqueous solution and under photoelectrochemical conditions.